The Influence of Accounting Conservatism and Economic Value Added on Corporate Equity Assessment. - Fitri Novalia; Marsellisa Nindito (Jurnal Ilmiah Wahana Akuntansi, 2016)
This research was intended to examine the influences of Accounting Conservatism and Economic Value Added toward Equity Valuation on manufacturing companies listed in Indonesia Stock Exchange. The independent variables used in this research were Accounting Conservatism and Economic Value Added. This research used secondary data that was obtained from the Indonesia Stock Exchange official website, which has been published in 2011 until 2013. The technique that was used to gather the sample was purposive sampling and there were 18 companies. Which all sample (N) in three years was 54 samples. Those 54 samples would analyse further in this research. The method used in this research was multiple linear regression analysis. The result of t-test showed that the first variable, accounting conservatism, had a negative and significant effect to equity valuation. The second variable, which was Economic Value Added, showed a positive and significant effect to equity valuation. The result of f-test accounting conservatism and Economic Value Added showed that both of them give simultaneously and significant effect to equity valuation. Key Words: Equity Valuation, Price Book Value, Accounting Conservatism, and Economic Value Added